New Forms of Exploitations in Neoliberal Capitalism: A Marxist Analysis (Khwopa Journal, 2026)
This paper argues that there are new forms of exploitations in neoliberal capitalism from Marxist lens. It promotes the concepts the labor flexibility, market efficiency, and individual autonomy. This study employs the qualitative methodology based on the secondary sources, including academic literatures, classical and contemporary Marxist scholarship, policy documents, and empirical studies addressing labor, finance, and digital economies with the applies of Marxist political economy as well as analytical framework to identify and synthesize recurring patterns, tensions, and contradictions within existing literature. The exploitations under neoliberal capitalism is no longer confined to conventional wage labor but increasingly operates through precarious employment arrangements, financial indebtedness, platform-mediated work, and unpaid reproductive activities. The aspects of neoliberalism in obscuring exploitative structures by portraying systematic inequalities as outcomes of individual choices and responsibilities. With the engaging with ongoing Marxist debates, the paper enhances understanding of the transformation of exploitation in the neoliberal era and reaffirms the significance of Marxist analysis for examining contemporary capitalist developments and their social consequences.